2009
DOI: 10.1590/s0004-282x2009000300037
|View full text |Cite
|
Sign up to set email alerts
|

Solving the conundrum of Job: a probable biblical description of chronic renal failure with neurological symptoms

Abstract: -The disease described in the Bible's Book of Job is controversial and had been of interest of theologists, psychiatrists, and dermatologists for many years. We describe several signs and symptoms compatible with chronic renal failure with neurological alterations.Key Words: bible, Job, chronic renal failure. Resolvendo o enigma de Jó: uma provável descrição bíblica de insuficiência renal crônica com sintomas neurológicosResumo -A doença descrita no livro bíblico de Jó é controversa, e tem interessado a teólog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is important to rule out systemic causes of neurological symptoms in COVID-19 patients, such as hepatic, renal failure, hypercapnia/hypoxic encephalopathies, coinfections, and treatment-related adverse effects, by blood gas analysis (ABG), liver and renal function tests, blood ammonia, evoked potential (EP), quantitative spectral electroencephalography (EEG) analysis, cerebrospinal fluid (CSF) test, magnetic resonance imaging (MRI), medication and treatment history, etc. (57)(58)(59)(60). Previous studies have found some red flags to suspect COVID-19 presence in patients with headache, such as fever, cough, systemic symptoms, prior medical history, some neurologic symptoms, and increased C-reactive protein (61).…”
Section: Auxiliary Tests For Nervous System Infections In Covid-19mentioning
confidence: 99%
“…It is important to rule out systemic causes of neurological symptoms in COVID-19 patients, such as hepatic, renal failure, hypercapnia/hypoxic encephalopathies, coinfections, and treatment-related adverse effects, by blood gas analysis (ABG), liver and renal function tests, blood ammonia, evoked potential (EP), quantitative spectral electroencephalography (EEG) analysis, cerebrospinal fluid (CSF) test, magnetic resonance imaging (MRI), medication and treatment history, etc. (57)(58)(59)(60). Previous studies have found some red flags to suspect COVID-19 presence in patients with headache, such as fever, cough, systemic symptoms, prior medical history, some neurologic symptoms, and increased C-reactive protein (61).…”
Section: Auxiliary Tests For Nervous System Infections In Covid-19mentioning
confidence: 99%
“…The adult onset of Job’s symptoms (as opposed to infancy, which also would have been fatal prior to intravenous immune globulin and antibiotics), and the lack of any noted family history of this dominant disorder makes this congenital disease a highly unlikely cause (the tragic death of his children, again after infancy, is due to attacking groups and to a mysterious “wind”). Scholars in the medical literature have proposed everything from kidney disease, 16 to primary dermatologic disorders, 17 , 18 to poisoning, 19 to psychiatric disorders, 20 , 21 and have taken to psychoanalyzing Job as well. 22 – 25 Nonetheless, it is valuable to ponder ancient encounters with disease and affliction, and contrast them to the modern ways that we understand, perceive, and deal with genetic diseases.…”
Section: Stat3lof Ad-hies As a Paradigm For Altering The Balance Of Pmentioning
confidence: 99%